Electronic and interface state density distribution properties of Ag/p-Si Schottky diode - Okutan, M; Basaran, E; Yakuphanoğlu, Fahrettin (Elsevier, 2005)
Electronic and interface state distribution properties of Ag/p-Si Schottky diode have been investigated. The diode indicates non-ideal current-voltage behavior with an ideality factor greater than unity. The capacitance-voltage (C-V) characteristic is linear in reverse bias indicating rectification behavior and charge density within depletion layer is uniform. From I-V and C-V characteristics, junction parameters such as diode ideality factor and barrier height were found as 1.66 and (phi(B(I-v)) = 0.84 eV (phi(B(C-V)) = 0.90 eV), respectively. The interface state density N-ss and relaxation time tau of the Schottky diode were determined by means of Schottky capacitance spectroscopy method. The results show the presence of thin interfacial layer between the metal and semiconductor. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Schottky diode; interface state density; conductance-capacitance technique